PENGARUH TINGKAT PENDAPATAN DAN PENGETAHUAN EKONOMI TERHADAP TINGKAT KONSUMSI MAHASISWA PROGRAM PASCASARJANA UNIVERSITAS NEGERI SURABAYA - Indrianawati, Entika; Soesatyo, Yoyok (UNIVERSITAS NEGERI SURABAYA, 2015)
The study aims to 1.) analyzing the Influence of the Income Level to Consumption Level In Post Graduate Students Universitas Negeri Surabaya, 2.) analyzing the Influence of the Economics Knowledge to Consumption Level In Post Graduate Students Universitas Negeri Surabaya, 3.) analyzing the Influence of the Income Level and the Economics Knowledge of Consumption Level In Post Graduate Students Universitas Negeri Surabaya. The population in this study were Post Graduate Students Universitas Negeri Surabaya, using proportional random sampling technique sampling. Methods of analysis using multiple regression analysis. The results showed that the level of income has partially significant effect on the level of student consumption Post Graduate Students Universitas Negeri Surabaya. Economics Knowledge negatively affect consumption levels Post Graduate Students Universitas Negeri Surabaya. Income levels and economic knowledge simultaneously have a significant effect on the level of student consumption Post Graduate Students Universitas Negeri Surabaya